USING INTERNET-RESOURCES FOR SCHOOL PHYSICS EXPERIMENTS - Nina P. Dementievska (Інформаційні технології і засоби навчання, 2012)
Using virtual computer simulation of physics processes and phenomena is becoming increasingly popular among teachers of science around the world. Such simulation for school experiment has several advantages, but teaching needs improvement of methodology for using in modern school. In order to computer simulations were successful in education it requires compliance with a number of conditions. Educators around the world collaborate on the web site Phet (http://phet.colorado.edu/), which provides science-based and effective computer simulations for studying the natural sciences in different languages, as well as the methodology for use in secondary school.